2012
DOI: 10.1007/s11250-012-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding sweet potato (Ipomoea batatas) vines as a supplement on feed intake, growth performance, digestibility and carcass characteristics of Sidama goats fed a basal diet of natural grass hay

Abstract: The objective of this study was to investigate the effects of substituting sweet potato [Ipomoea batatas (L) Lam] vines for concentrate on growth performance, digestibility, and carcass characteristics. Thirty yearling bucks (15.3 ± 1.64 kg) were assigned into six treatments in a randomized complete block design: natural grass hay alone (T1) or supplemented with 100 % sweet potato vines (SPV) (T2), 65 % SPV + 35 % concentrate (T3), 35 % SPV + 65 % concentrate (T4), and 100 % concentrate (T5) on dry matter (DM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
4
17
1
Order By: Relevance
“…Comparable to the NDF content of WB in the present study, values of 484 g/kg DM by Gebeyew et al (2015) and 480.1 g/kg DM by Gebru et al (2015) were documented. The ADF content of WB in this study was greater than the value of 105 g/kg DM reported in earlier study (Megersa et al, 2013). It has been noted that fiber content of WB may vary depending upon the quality of wheat being milled and the exact processing method used (Tolera, 2008).…”
Section: Chemical Composition Of Experimental Feedscontrasting
confidence: 65%
“…Comparable to the NDF content of WB in the present study, values of 484 g/kg DM by Gebeyew et al (2015) and 480.1 g/kg DM by Gebru et al (2015) were documented. The ADF content of WB in this study was greater than the value of 105 g/kg DM reported in earlier study (Megersa et al, 2013). It has been noted that fiber content of WB may vary depending upon the quality of wheat being milled and the exact processing method used (Tolera, 2008).…”
Section: Chemical Composition Of Experimental Feedscontrasting
confidence: 65%
“…Sweet potato branches and leaves is being a practive adopted by small growers to complement animal feed, after roots consumption. Sweet potato branches and leaves used animal feed supply showed promising results for dairy cows (Khalid et al, 2013), goats (Megersa et al, 2013) and pigs (Peters, 2004). Sweet potato branches good performance can be linked to its high protein content, which is between 26-33%, and with considerable amounts of vitamins A, B2,…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (Claessens et al, 2008;Larbi et al, 2007;Megersa et al, 2012;Mussoline and Wilkie, 2017) evaluated the potential of using sweet potato as a dual-purpose crop, i.e. harvesting the aboveground biomass as fodder for livestock feed and harvesting the storage root for human consumption.…”
Section: Introductionmentioning
confidence: 99%